Core Self-Evaluations Increases Among Chinese Employees: A Cross-Temporal Meta-Analysis, 2010–2019 - Lin, Xinqi; Luan, Yuxiang; Zhao, Guolong; Zhao, Teng; Ding, He (Frontiers in Psychology, 2022)
The purpose of this paper is to investigate the changes in core self-evaluations (CSE) scores among Chinese employees during 2010-2019. We conducted a cross-temporal meta-analysis including 50 studies (17400 Chinese employees) to evaluate the relationship between the year of data collection and levels of CSE. We found that correlations between levels of CSE and year of data collection were strong and positive (r > 0.500). Regression results showed the year of data collection could predict CSE score when mean sample age and sex ratio (%female) were controlled. In addition, CSE scores were positively related to GDP per capita and negatively related to the unemployment rate.